1961
DOI: 10.1002/pol.1961.1205115513
|View full text |Cite
|
Sign up to set email alerts
|

The cellulose–butadiene diepoxide reaction and its effect on the crease resistance of cotton

Abstract: Butadiene diepoxide (BDE), the meso‐1,2,3,4‐diepoxybutane, may be added to cotton cellulose with a variety of catalysts and conditions at room temperature. A slow addition of BDE from nonpolar solvents to yarns pretreated with alkali resulted in weight gains which were proportional to the activity of hydroxyl ions used in pretreatment. For a given hydroxyl ion activity, percentage weight gains of BDE varied directly with time of reaction. Add‐on of BDE has been shown to be proportional to the product of hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1963
1963
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Microscopists usually speak of degrees or levels of cross-linking, meaning that some derivatives of a low degree of substitution swell more than do those with higher D.S. The Form D and Form W processes for treating cotton are cases in point, as is also treatment with BDE ( meso-butadiene diepoxide) [40]. From the electron micrographs in this latter work it was shown that different degrees of dissolution and swelling occurred with samples having the same crease angles.…”
Section: Cotton Cell Ulose ~And Water 'mentioning
confidence: 88%
See 1 more Smart Citation
“…Microscopists usually speak of degrees or levels of cross-linking, meaning that some derivatives of a low degree of substitution swell more than do those with higher D.S. The Form D and Form W processes for treating cotton are cases in point, as is also treatment with BDE ( meso-butadiene diepoxide) [40]. From the electron micrographs in this latter work it was shown that different degrees of dissolution and swelling occurred with samples having the same crease angles.…”
Section: Cotton Cell Ulose ~And Water 'mentioning
confidence: 88%
“…' 4. E~o.rides and Wet Creasr R~~oz~c~r~Õ ne must exercise care in comparing epoxide finishes with formaldehyde finishes, because here we are dealing with a class of compounds that vary widely in reactivity for reasons pointed out previously [36,38,40].…”
Section: Cotton Cell Ulose ~And Water 'mentioning
confidence: 99%
“…Due to the pseudo basicity of epoxides, hydroxyl ions are generated after the initial r~ng openings by chloride ions, and this can be considered as an alkaline catalyzed reaction. Certain epoxides have been found to add to cotton cellulose when catalyzed by 1 M NaCI under these conditions [13]. At reasonable add-ens, there was little irn-…”
Section: Tepa Treatmentsmentioning
confidence: 96%
“…In one series, the fabric was pretreated by twice padding to approximately 95% wet pickup with an aqueous solution of catalyst (NaOH or salt) and then immersed in a CCI, solution of the triepoxide. Previously, similar application of butadiene diepoxide had produced the desired results [2,13].…”
Section: Application Of Tepa To Fabricsmentioning
confidence: 99%
“…Actually, McKeZvey et al 3,13) have found that the percentage of "add-on" for yarns treated with a 20% solution of 1,2,3,4-diepoxybutane in carbon tetrachloride for 16 h at 26°C increases linearly with the increase in activity of the OHion up to a maximum, which is reached at concentrations of sodium hydroxide between 13 and 15%. Tab.…”
Section: Effect Of Catalystmentioning
confidence: 99%